Punk Biographical Narratives in Latin America and Their Connection to Authoritarian Periods; [Narrativas Biográficas Punk en Latinoamérica y Su Conexión Con Períodos Autoritarios] - Perez-Seballos, S (HISIN (History of Information Systems), 2024)
Introduction: This article analyzes Latin American punk biographical discourses, focusing on their relationship with periods of violence and authoritarianism, especially the remnants of dictatorial periods. Methodology: A comparative analysis of three punk biographical works from Argentina, Peru, and Chile: “Uno, dos, Ultraviolento: la historia de Los Violadores,” “Kloaka y los Subterráneos: el instinto de vivir,” and “NN: recuerdos de un amigo del caos.” A semiotic textual analysis is used, considering the presence of violence, the themes addressed, and the narrative decisions within the texts. Results: The three biographical works analyzed contain a variety of genres and narrative influences, combining traditional biographical elements with narrative and stylistic decisions that challenge this structure, notable for their fragmentariness. Discussions: The works reflect the essence of punk by incorporating politics, art, memory, action, and disruptive culture. Similar to fanzines, graphic art, and punk songs, they present complex messages that transcend biographies. Conclusions: The fragmentariness and the departure from the "hero s journey" are highlighted, showing how violence and authoritarian structures influence these narratives. It is suggested to expand future research to more works and territories. © 2024, HISIN (History of Information Systems). All rights reserved.